Low Serum Magnesium Levels Are Associated With Hemorrhagic Transformation After Thrombolysis in Acute Ischemic Stroke - Cheng, Zicheng; Huang, Xiaoyan; Muse, Farah Mohamed; Xia, Lingfan; Zhan, Zhenxiang; Lin, Xianda; Cao, Yungang; Han, Zhao (Frontiers in Neurology, 2020)
Background: In patients with acute ischemic stroke, hemorrhagic transformation is a major complication after intravenous thrombolysis. This study aimed to investigate the relationship between serum magnesium levels and hemorrhagic transformation (HT) after thrombolytic therapy. Methods: We retrospectively analyzed data from 242 patients who received thrombolytic therapy at the Second Affiliated Hospital of the Wenzhou Medical University in China. Baseline serum magnesium levels were measured before intravenous thrombolysis, and the occurrence of HT was evaluated using computed tomography images reviewed within 24-36 h after therapy. The relationship between serum magnesium levels and HT was examined using multivariate logistic regression, subgroup analysis, and restricted cubic spline models. Results: Of the 242 included patients, 43 (17.8%) developed HT. Patients with HT had significant lower serum magnesium levels than those without HT (0.81 ± 0.08 vs 0.85 ± 0.08 mmol/L, p = 0.007). Multivariable logistic regression analysis indicated that patients with higher serum magnesium levels had lower risk of HT (OR per 0.1-mmol/L increase 0.43, 95% CI 0.27-0.73, p = 0.002). However, this association did not persist when baseline levels of serum magnesium were higher than the median value (0.85 mmol/L) in subgroup analysis (OR per 0.1-mmol/L increase 0.58, 95% CI 0.14-2.51, p = 0.47). This threshold effect was also observed in the restricted cubic spline model when serum magnesium levels were above 0.88 mmol/L. No association between symptomatic HT and serum magnesium levels was observed in our study (OR per 0.1-mmol/L increase 0.52, 95% CI 0.25-1.11, p = 0.092). Conclusions: Lower serum magnesium levels in patients with ischemic stroke are associated with an increased risk of HT after intravenous thrombolysis, but perhaps only when serum magnesium is below a certain minimal concentration.